Some Ideas about Viewer Re-Mobilization from a Practice-in-Progress - Couroux, Marc (Circuit, 2006)
This article presents a practical view of one artist's dealings with the social and political aspects of the concert, seen through a variety of works realized between 1999 and 2006. Couroux's work is centered around the reintegration of the listener-viewer into the social event, specifically the concert format, which has functioned as a control group, enabling him to test some ideas about viewer mobilization. Exploring the potential of art as a motor for social investigation, he exploits the perceptual and cultural prejudices of the viewer to create a productive, creative zone of inquiry. A brief history of anti-virtuosity begins the article (with examples from Xenakis, Barrett, Ferneyhough and Glenn Gould, all of whom have called into question in various ways the totalized persona of the performer), ushering in the feedback processes of his work American Dreaming and the anti-absorptive strategies which underlie le contrepoint académique (sic). Finally, the position of the listener is problematized in two works: Blowback at Breakfast, in which he/she is enmeshed in a panopticon-like voyeuristic bind with the performer, and Watergating, in which shifting modes of aurality force a deconstruction of the listening process itself.